STRATEGIC FINANCIAL INTELLIGENCE IN THE DIGITAL AGE: HARNESSING ADVANCED DATA ANALYTICS FOR INFORMED DECISION-MAKINGAMIDST COMPLEX BUSINESS LANDSCAPES - Irwan Sugiarto (CV. Adiba Aisha Amira, 2025)
In the contemporary business landscape, the amalgamation of strategic financial intelligence and advanced data analytics stands as a linchpin for organizations navigating the complexities of the digital age. This study explores the interplay between these elements, focusing on how organizations harness data analytics for informed decision-making amidst intricate business environments. The imperative to make strategic financial decisions has catalyzed a paradigm shift, prompting organizations to leverage cutting-edge data analytics tools. The literature review encapsulates vital findings, highlighting the transformative potential of data analytics in reshaping risk management, fostering predictive modeling, and enhancing overall organizational effectiveness. As organizations strive to adapt to dynamic market conditions, the insights derived from this study provide a foundation for future research and practical implementations. This abstract encapsulates the essence of our exploration into strategic financial intelligence, underscoring its pivotal role in the digital age and its symbiotic relationship with advanced data analytics.